Middle-Class Entrepreneurs and Social Mobility through Entrepreneurship in Colombia - Paula Mejia; Marcela Melendez (Inter-American Development Bank (IDB), 2012)
The paper uses microeconomic data to characterize entrepreneurs by income group and selected household, individual and business characteristics, finding that entrepreneurship is rare but more frequent in the upper class than the middle or lower classes. Middle-class entrepreneurs are, on average, better off than middle-class employees of similar characteristics but differ greatly from upper-class entrepreneurs in terms of educational attainment, the size of their businesses, and their outcomes. While entrepreneurs appear to have more income mobility than the average worker, this paper cannot establish whether this is true for middle-class entrepreneurs in particular, nor provide evidence to support the hypothesis that middle-class entrepreneurs activity is an engine for economic growth. Instead, the findings suggest that the types of businesses run by these entrepreneurs are characterized by low productivity. Consequently, policies to increase social mobility seem to hold greater promise for promoting higher productivity and welfare than policies encouraging entrepreneurship.
Keywords: I31; L26; O12; 330